PREVALENCE OF EXTENDED SPECTRUM BETA-LACTAMASES (ESBLS) PRODUCING ESCHERICHIA COLI AND KLEBSIELLA PNEUMONIAE AMONG HOSPITALIZED PATIENTS FROM NIGERIA - Egbule, Olivia Sochi; Ejechi, Bernard O. (FUDMA JOURNAL OF SCIENCES, 2021)
The aim of this study was to determine the resistance patterns and ESBLs production among clinical isolates of Escherichia coli and Klebsiella pneumoniae in two government hospitals of Delta State, Nigeria. Urine, blood and wound samples were aseptically collected from hospitalized patients, bacteriologically processed and isolates identified using standard protocols. Antimicrobial susceptibility testing was determined by disc diffusion method. The plasmid DNA of Multidrug resistance (MDR) isolates were extracted by alkaline lysis method. Phenotypic ESBL production of the MDR isolates was done by Double Disc Synergy Test (DDST) while PCR was used to detect blaCTX-M, blaSHV and blaTEM among isolates. A total of 217 isolates were obtained, of which 161(74.2%) and 56(25.8%) were Escherichia coli and Klebsiella pneumoniae respectively. The antimicrobial resistance varied from one location to another. All isolates obtained from blood of general hospital Warri (GHW) were 100% resistant to amoxicillin clavulanic acid and the cephalosporins (ceftazidime, cefotaxime, and cefuroxime). Isolates from General hospital Agbor (GHA) showed high resistance of 75.0% to cefotaxime, 93.8% to each of ceftazidime and cefuroxime. Overall low resistance to nitrofurantoin was observed in E. coli isolates obtained from urine of GHW (27.5%) and GHA (20.8%). Out of 217 isolates, 75.1% (163/217) were MDR, of which 36.8% and 39.3% produced ESBL by DDST and PCR respectively. The most common ESBL gene was blaCTX-M expressed by 28(17.2%) of the isolates. The high prevalence of MDR and ESBL underscores the need for a continuous local monitoring of antibiotic resistance.
Keywords: antibiotics, Multidrug-Resistance (MDR), ESBL production, Klebsiella pneumoniae, Escherichia coli.